Optimizing Google Documents as an Innovation Media for Effective and Sustainable School Literacy Habits - Siti Arofah; Wiwin Yulianingsih; M. Syahidul Haq (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The low reading literacy achievement of Indonesian students, as reflected in the 2022 Programme for International Student Assessment (PISA) scores and the Education Report of SMAN 1 Ngoro Mojokerto, demonstrates the need for strategic innovation in strengthening school literacy culture. Reading and writing literacy are the main foundations for developing critical, reflective, and communicative thinking skills needed to realize the vision of Golden Indonesia 2045. This innovation project aims to (1) describe the understanding of SMAN 1 Ngoro Mojokerto residents regarding the importance of literacy, (2) analyze the implementation of the ongoing literacy culture, and (3) formulate strategies for improving literacy culture through the use of digital technology. The method used is a descriptive-qualitative approach based on best practices with document analysis, Education Report data, and evaluation of innovation programs. The innovation developed is the